Strengthening Religious Values ​​for the Self-Development of Students at MPU Gedongan Colomadu Elementary School - Dita Yuliana; Khuriyah Khuriyah (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to examine religious strengthening in shaping the character of students at SD MPU Gedongan Colomadu. In an educational environment based on Islam, instilling religious values ​​is a must in shaping the character of superior students. The method used in this study is a qualitative type with observation, interview and documentation techniques. Informants in this study include the principal, religious deputy, curriculum deputy, teachers and students. Based on the results of the study, efforts to strengthen religion carried out by SD MPU Gedongan include: congregational prayer, praying before doing activities, getting used to praying Dhuha, giving alms and advice, in addition, the influence of teachers has a significant role in guiding and setting an example for students.